2011
DOI: 10.15669/pnst.2.232
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of MCNP5 Dose Calculations inside the RANDO® Phantom Irradiated with a MLC LinAc Photon Beam against Treatment Planning System PLUNC

Abstract: MC treatment planning techniques provide a very accurate dose calculation compared to 'conventional' deterministic treatment planning systems. In the present work, PLanUNC (PLUNC), a set of software tools for radiotherapy treatment planning (RTP), is compared with MCNP5 (Monte Carlo N-Particle transport code) by calculating dose maps inside the RANDO ® phantom, utilized as the patient model, irradiated with different field sizes with the MultiLeaf Collimated (MLC) Linear Accelerator (LinAc) Elekta Precise. PLU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…According to the International Commission on Radiological Protection (ICRP)'s Publication No.60 [4], the skin dose should be assessed for the dermis and epidermis layers of the skin. Although we are able to estimate dose to a patient using the radiation treatment planning system (TPS) [5] [6] [7], a number of studies have demonstrated that surface and near-surface doses estimated by TPS can be inaccurate [8] [9] [10]. One reason is the steep dose gradient in this region.…”
Section: Introductionmentioning
confidence: 99%
“…According to the International Commission on Radiological Protection (ICRP)'s Publication No.60 [4], the skin dose should be assessed for the dermis and epidermis layers of the skin. Although we are able to estimate dose to a patient using the radiation treatment planning system (TPS) [5] [6] [7], a number of studies have demonstrated that surface and near-surface doses estimated by TPS can be inaccurate [8] [9] [10]. One reason is the steep dose gradient in this region.…”
Section: Introductionmentioning
confidence: 99%